2017
DOI: 10.1002/cld.678
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton pump inhibitors in chronic liver diseases

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/10-6-reading-li.html a video presentation of this article http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/10-6-interview-chung.html the interview with the author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…PPIs inactivate NA + -K + -ATPase, thereby inhibiting gastric acid secretion, reducing the injury caused by gastric acid to the mucosa, and promoting postoperative ulcer healing[ 19 ]. Although reports have suggested that long-term application of PPIs might increase the occurrence of spontaneous peritonitis and hepatic encephalopathy in patients with liver cirrhosis[ 20 - 22 ], a recent clinical study determined that routine application of PPIs for 30 d after EVL was safe and could significantly reduce the upper gastrointestinal rebleeding and mortality rates of patients within 30 d of hospitalization[ 16 ]. Meanwhile, a recent meta-analysis also showed that PPI reduced the rebleeding rate of patients with liver cirrhosis and esophagogastric variceal bleeding by nearly 50% after endoscopic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…PPIs inactivate NA + -K + -ATPase, thereby inhibiting gastric acid secretion, reducing the injury caused by gastric acid to the mucosa, and promoting postoperative ulcer healing[ 19 ]. Although reports have suggested that long-term application of PPIs might increase the occurrence of spontaneous peritonitis and hepatic encephalopathy in patients with liver cirrhosis[ 20 - 22 ], a recent clinical study determined that routine application of PPIs for 30 d after EVL was safe and could significantly reduce the upper gastrointestinal rebleeding and mortality rates of patients within 30 d of hospitalization[ 16 ]. Meanwhile, a recent meta-analysis also showed that PPI reduced the rebleeding rate of patients with liver cirrhosis and esophagogastric variceal bleeding by nearly 50% after endoscopic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) reduce gastric pH and motility and promote small intestinal bacterial overgrowth. 83 PPIs (especially prolonged use) increase the risk of infections, such as SBP and C. difficile in cirrhosis, and adversely affect the outcomes. 84 85 86 Hence, it may be prudent to avoid long-term PPIs in patients with cirrhosis.…”
Section: Primary Preventionmentioning
confidence: 99%
“…PPIs are extensively used in individuals with cirrhosis without clear indications 2 . There have been concerns about the PPIs use in cirrhotic patients.…”
mentioning
confidence: 99%